Design and experimentation of the nested pneumatic soft actuator for hand exoskeleton - Yi Lv; Zaiming Geng; Hao Wu; Yigang He; Zhongming Lv (Journal of Engineering and Applied Science)
Abstract Frequent repetitive manual tasks in the manufacturing industry have contributed to a rise in hand motor dysfunction, negatively affecting both health and work efficiency. While rigid hand exoskeleton robots are effective, they are often heavy and may cause secondary injuries. In contrast, soft hand exoskeleton robots demonstrate significant potential as tools for injury prevention and assistance. This paper presents a hand-wearable pneumatic soft robot designed to assist in daily hand activities and prevent muscle atrophy. The developed soft actuator features a nested structure with uniformly distributed cross-sectional shapes of the internal pneumatic chamber. A constraining shell, made of materials with a different elastic modulus than the main structure, is placed around the pneumatic chamber to limit radial expansion. Based on the general structural parameters of the cross-sectional shape, a physical model was established to simulate bending conditions. The actuator prototype was fabricated using a multistep casting method. During experiments, at an air pressure of 43 kPa, the actuator achieved an average bending angle of 260 ± 5° and an average output force of 6.0 ± 0.1 N. The soft actuator was integrated into a wearable hand robot for further testing. Results demonstrate that it effectively supports finger flexion and object grasping while helping to reduce muscle fatigue.